Plant Row Spacing Effect on Growth and Yield of Green Pepper (Capsicum annuum L.) in Western Kenya - Ocharo N. Edgar; Joseph P. Gweyi-Onyango; Nicholas K. Korir (Archives of Current Research International, 2017)
Green pepper production based on the package of recommendations developed has not given the desired growth and yield performances in the world and specifically Kenya. Information is required with which to evolve the agronomic practices that will be adopted to maximize yield in green pepper production. Great attention should be paid when selecting the most appropriate spacing where there are very few reports and limited information regarding plant spacing in cultivation of the crop under the agro-climatic conditions of Kenya. Therefore, a field study was carried out at the Alupe Research Station, Busia County, to evaluate the growth and yield responses of green pepper under three row plant spacings namely: 50x40 cm, 40x40 cm and 30x40 cm during the long and short rainy seasons of 2015. The experiment was set up in a randomized complete block design with three replicates. The treatment effects were measured on plant growth for 12 weeks and ripe fruit yield parameters which were later cleaned statistically analyzed. The plant spacing had significant variation in almost all the growth and yield components except the fruit length. In both seasons, the number of branches per plant, stem girth and number of fruits per plant were found to be significantly increased with the increasing of plant spacing but the plant height, number of leaves per plant, fruit breadth and yield per plant were found to be significantly increased with the decreasing plant spacing. The highest yield per plant of 555.1 g and 551.8 g were realized during the short and long rainy seasons respectively in the 40 by 40 cm spacing treatment. Considering the yield of fruits per plant, the 40 by 40 cm plant spacing appeared to be the most recommendable for the cultivation of green pepper.